Reducing the Human and Environmental Risks of Obsolete Pesticides : A GIS-Based Tool for Priority-Setting - World Bank (Washington, DC, 2017)
Obsolete pesticide stocks have accumulated in most of the world's developing countries and economies in transition in recent decades. International organizations estimate that some 500,000 tons are stockpiled worldwide, about half of which are located in countries of the former Soviet Union. Across the African continent, obsolete stocks total about 50,000 tons, while Latin America has at least 30,000 tons. This report includes the following sections: section one includes overview, section two include risk assessment method for priority-setting. Section three includes setting cleanup priorities in Tunisia. Section four includes cleanup and safeguarding highlights in Africa. Finally, section five includes reducing the risk.